THE EFFECT OF ALLOY ELEMENTS ON FATIGUE STRENGTH OF GRAY CAST IRON AT ROOM AND HIGH TEMPERATURE - Sulardjaka, Sulardjaka; Atmaja, Sugeng Tirta; Nugroho, Sri; Adnan, F; Cahyono, A. D. (ROTASI, 2013)
Gray cast iron is quite poor in terms of fatigue resistance due to its typical microstructure of distributed graphite lamellas in a pearlite matrix. The objective of this research to improve mechanical properties and fatigue strength gray cast iron (GCI) at high temperature by adding the alloy elements such as: nickel (Ni), molybdenum (Mo), copper (Cu) and chromium (Cr). The mechanical characterization that has been done is tensile test and hardness tesst. The tensile test was conducted based on ASTM E8 standard. The hardess test of GCI was test by Brinell Hardness Test methods based on ASTM E10. Fatigue test was performed on continuous radius fatigue specimens based on JIS Z 2774 standard with cyclic loading frequency of 50 Hz and load ratio R = -1. The fatigue test has been done at room temperature and at temperature 300oC. The results of this experiments show that alloy elements such as : nickel (Ni), molybdenum (Mo), copper (Cu) and chromium (Cr) increase the hardness and tensile strength of Gray cast iron. Nickel results finer graphite grain and improve fatigue strength of Gray cast iron at high temperature.